2011
DOI: 10.1002/hep.24028
|View full text |Cite
|
Sign up to set email alerts
|

CXC chemokine receptor-1 is expressed by hepatocytes and regulates liver recovery after hepatic ischemia/reperfusion injury

Abstract: CXC chemokines mediate hepatic inflammation and injury following ischemia/reperfusion (I/ R). More recently, signaling through CXC chemokine receptor-2 (CXCR2) was shown to delay liver recovery and repair after I/R injury. The chemokine receptor CXCR1 shares ligands with CXCR2, yet nothing is known about its potential role in liver pathology. In the present study, we examined the role of CXCR1 in the injury and recovery responses to I/R using a murine model. CXCR1 expression was undetectable in livers of sham-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 68 publications
5
41
0
Order By: Relevance
“…The activities of physiological processes reflected by expression changes were analyzed by systems biology methods, and both the chemotactic factor branches and its regulation of hepatocyte proliferation activity were found increased in rat liver regeneration (Figure 1). This result was consistent with the conclusion of Van Sweringen et al (2011), who demonstrated the correlation between the signal transduction activity of the chemotactic factor branch of the NF-κB signaling pathway and hepatocyte proliferation activity (Clarke et al, 2011;Van Sweringen et al, 2011). The above results led to the speculation that the downregulation of Cxcl12 and upregulation of its receptor-activated gene Gnail and its homologous genes Bf289002 together activate transcription factor NF-κB family member Rela's homologous gene Bf419700, which augment hepatocyte proliferation activity by upregulating the expression of cell proliferation-promoting genes Ccnd1, Myc, and Timp1 and downregulating the expression of cell proliferation-inhibiting gene Dusp1, ultimately enhancing hepatocyte proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…The activities of physiological processes reflected by expression changes were analyzed by systems biology methods, and both the chemotactic factor branches and its regulation of hepatocyte proliferation activity were found increased in rat liver regeneration (Figure 1). This result was consistent with the conclusion of Van Sweringen et al (2011), who demonstrated the correlation between the signal transduction activity of the chemotactic factor branch of the NF-κB signaling pathway and hepatocyte proliferation activity (Clarke et al, 2011;Van Sweringen et al, 2011). The above results led to the speculation that the downregulation of Cxcl12 and upregulation of its receptor-activated gene Gnail and its homologous genes Bf289002 together activate transcription factor NF-κB family member Rela's homologous gene Bf419700, which augment hepatocyte proliferation activity by upregulating the expression of cell proliferation-promoting genes Ccnd1, Myc, and Timp1 and downregulating the expression of cell proliferation-inhibiting gene Dusp1, ultimately enhancing hepatocyte proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…CXC chemokines containing the ELR motif bind to the receptors CXCR1 and CXCR2 and have been shown regulate liver repair and regeneration [511]. Of particular interest is the fact that this ligand/receptor system has been shown to have divergent effects on liver regeneration that is dependent upon the insult.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that specific members of the CXC chemokine family are critical mediators in all aspects of the injury, repair, and regeneration processes (2,4,5,17). Our previous work focused on CXC chemokines that contain a glutamic acid-leucinearginine (ELR) motif in their amino terminus, which confers binding specificity to the receptors CXCR1 and CXCR2 (2,17). However, other CXC chemokines may also be involved in the response to hepatic I/R injury.…”
mentioning
confidence: 97%
“…The ischemic insult induces an inflammatory response resulting in acute liver injury that is followed by a reparative phase and subsequent liver regeneration mediated by a complex interaction of growth factors, cytokines, and transcriptional factors (7,22). We previously showed that specific members of the CXC chemokine family are critical mediators in all aspects of the injury, repair, and regeneration processes (2,4,5,17). Our previous work focused on CXC chemokines that contain a glutamic acid-leucinearginine (ELR) motif in their amino terminus, which confers binding specificity to the receptors CXCR1 and CXCR2 (2,17).…”
mentioning
confidence: 98%